GIS-Based Flood Risk Mapping in Kluet Tengah Subdistrict, South Aceh - Helmi Hasan Basri; Bakruddin B (International Journal of Multidisciplinary Sciences and Arts, 2026)
Flooding is one of the most frequent hydrometeorological disasters in South Aceh Regency, particularly in Kluet Tengah Subdistrict, where overflow from the Menggamat River causes recurrent inundation of settlements, agricultural areas, and other land uses. This study aims to map flood risk spatially in Kluet Tengah Subdistrict using a Geographic Information System (GIS)-based overlay approach. The analysis was conducted using land cover and slope parameters derived from satellite imagery, Digital Elevation Model (DEM) data, and supporting records of flood events from relevant disaster management agencies. Spatial data were processed through clipping, classification, and overlay analysis to produce flood risk categories. The results show that high-risk areas are concentrated in lowland zones with flat to gentle slopes (0–30%), particularly in settlements, rice fields, and open land. Moderate-risk areas are associated with moderately steep slopes (30–50%) dominated by mixed gardens and shrubland, while low-risk areas are mainly located in steep to very steep uplands (>50%) covered by protected forest and the Gunung Leuser National Park area. These findings indicate that the interaction between land cover and slope plays an important role in shaping flood risk distribution in the study area. The resulting flood risk map can support spatial planning, disaster mitigation, and sustainable land management in flood-prone regions of South Aceh.